Taxonomic Murder and Ethical Practice: A Reply to Alf and Wieneke (2023) on the Taxonomic State of Lambis vertriesti Dekkers & Maxwell, 2022 (Neostromboidae; Strombidae) and a Range Extension for that Species - Maxwell, Stephen J. (European Journal of Applied Sciences, 2023)
Lambis vertriesti ranges from the Philippines into Indonesia. Lambis species in general are highly plastic in form, and comparison should be drawn based on holotype material for accuracy. The use of a regionalised form that is morphologically incompatible from the holotype is theoretically unsound. Significant morphological features differentiate L. vertriesti from Lambis lambis and the synonymisation of those species by Alf and Wienke is unwarranted.